Chromosomal aberrations by fluorescence in situ hybridization (FISH)--Biomarker of exposure to carcinogenic PAHs - Beskid, Olena; Binková, Blanka; Dušek, Zdík; Rössner, Pavel; Solanský, Ivo; Kalina, Ivan; Židzik, Jozef; Popov, Todor A; Farmer, Peter B; Šrám, Radim J (Mutation research. Fundamental and molecular mechanisms of mutagenesis, 2007)
The fluorescence in situ hybridization (FISH) technique with whole chromosome painting for chromosomes #1 and #4 was used to study the impact of air pollution containing higher concentrations of carcinogenic polycyclic aromatic hydrocarbons (c-PAHs) in three European cities, Prague (Czech Republic), Kosice (Slovakia) and Sofia (Bulgaria). In each site were followed an exposed group, who were police officers or bus drivers who work usually through busy streets for at least 8h, and a reference group, who spent more than 90% of their daily time indoors. In Prague, a significant increase was observed in percentage of aberrant cells (% AB.C.) in the police officers compared to the reference group (0.33+/-0.25 versus 0.24+/-0.18, p<0.05). In Kosice, the exposed group differed from reference in the endpoints F(G)/100 1.52+/-1.18 versus 1.12+/-1.30, p<0.05; % AB.C. 0.30+/-0.19 versus 0.21+/-0.20, p<0.05; t/1000 3.91+/-3.18 versus 2.84+/-3.10, p<0.05. In Sofia were followed two exposed groups: police officers and bus drivers. All FISH endpoints were significantly higher in police officers compared to reference group (F(G)/100 1.60+/-0.99 versus 0.82+/-0.79, p<0.01; % AB.C. 0.25+/-0.14 versus 0.13+/-0.13, p<0.01; t/1000 4.19+/-2.65 versus 2.13+/-2.05, p<0.05; rcp 1.46+/-1.07 versus 0.70+/-0.76, p<0.05). In bus drivers compared to reference there was an increase in % AB.C. (0.25+/-0.18 versus 0.13+/-0.13, p<0.05). This is the first study when FISH method was used to analyze the impact of environmental air pollution. According to the original hypothesis it is expected that the most important group of chemicals responsible for the biological activity of air pollution represent c-PAHs.
Keywords: financování organizované; dospělí; karcinogeny životního prostředí; biologické markery; Biomarkers; Adult; monitorování životního prostředí; Police; lidé; Occupational Exposure; Financing, Organized; Male; pracovní expozice; chromozomální aberace; Air Pollutants; polycyklické aromatické uhlovodíky; Polycyclic Aromatic Hydrocarbons; Environmental Monitoring; hybridizace in situ fluorescenční; mužské pohlaví; policie; In Situ Hybridization, Fluorescence; látky znečišťující vzduch; Chromosome Aberrations; Carcinogens, Environmental; Humans